Assessment of Neck Lumps in Relation to Dentistry. Issue 3 (August 2017) - Siddiqui, Sarah; Osher, Jonas
Neck lumps have a varied aetiology, from a benign inflammatory cause to the first presenting sign of a malignancy. Patients may present to primary care complaining of a neck lump or they may be identified as an incidental finding during routine examination. This article highlights a structured approach to the initial assessment including history taking, risk factor assessment and clinical examination. Further investigations undertaken in a secondary care setting, such as ultrasound and guided fine needle aspirations, are then discussed. The common congenital, inflammatory, infective, vascular and neoplastic causes of neck lumps and their management and specialist referral pathway are discussed.